A Review of Tomography System - Juliza Jamaludin; Mohd Zikrillah Zawahir; Ruzairi Abdul Rahim; Fazlul Rahman Mohd Yunus; Nor Muzakkir Nor Ayob; Muhammad, Suzzana Ridzuan Aw; Naizatul Shima Fadzil; Zulkarnay Zakaria; Mohd Hafiz Fazalul Rahiman (Penerbit Universiti Teknologi Malaysia (Penerbit UTM Press), 2024)
Vol. 64 No. 5: Special Edition